Interferons in HIV-1 infection: mechanisms, antiviral potentials, and therapeutic challenges - Zhu, Luying; Ji, Jiahao; Xiao, Jing; Wang, Fuchun; Yu, Jiaqi; Liu, Yanmin; Zhang, Yang; Wu, Hao; Su, Bin; Lu, Xiaofan; Zhang, Tong (Frontiers in Immunology, 2025)
Type I interferons (IFNs), particularly IFN-α, occupy a central paradox in HIV-1 infection: they provide an essential early antiviral barrier that limits initial dissemination, yet their sustained activation contributes to chronic immune activation, CD4+ T-cell dysfunction, and incomplete viral control. This duality—protective in acute infection but pathogenic during chronic disease—remains a major unresolved challenge for interferon-based therapeutic strategies in HIV-1. Recent advances in ISG functional profiling, IFN-α subtype–specific antiviral potency, and the development of targeted innate-pathway modulators (e.g., STING-selective agonists, ncRNA regulators, TLR7 activators) have renewed interest in reevaluating interferon-centered approaches. These developments make it timely to reassess whether IFN-α can be safely and effectively integrated into modern HIV-1 therapeutic concepts, particularly in early-infection windows or in rationally designed combination regimens. In this review, we synthesize current knowledge of interferon-mediated restriction mechanisms, the hierarchy of key antiviral ISGs (e.g., APOBEC3G, MX2, BST2), and HIV-1 evasion of the JAK–STAT and cGAS–STING pathways. We further analyze how dose, timing, and IFN-α subtype contribute to divergent antiviral versus inflammatory outcomes across different stages of infection. Emerging precision strategies that modulate interferon signaling without triggering systemic inflammation offer promising translational directions. Balancing antiviral efficacy with immune homeostasis will be essential for developing next-generation interferon-based interventions aimed at durable control or functional cure of HIV-1 infection.